Structure and Composition of Tree Islands and Krummholz within the Forest-Tundra Ecotone in Central and Eastern Canada - Albertsen, Elena; Harper, Karen; De Fields, Danielle (ARCTIC, 2014)
The forest-tundra ecotone is expected to experience some of the initial effects of climate change. At the forefront of this transition zone, we find clonal growth forms of stunted and deformed trees with and without taller erect trees, called tree islands and krummholz, respectively. We sought to assess the potential effects of expansion of these clonal growth forms on tundra plant species at two Canadian locations, one in the Mealy Mountains of Labrador and the other near Churchill, Manitoba. Our objectives were 1) to analyze the structure (height distribution and shape) of these clonal growth forms to determine whether they are expanding; 2) to compare tree cover on the leeward and windward sides of clonal growths and 3) to assess patterns in individual plant species across these growth forms. Cover of trees and other plant species was measured at both locations, while tree stems were mapped near Churchill only. The presence of seedlings and symmetric patterns of tree height suggest that half of the tree islands near Churchill may be expanding. The edges of tree islands and krummholz may harbour safe sites for tundra plant species, as shown by peaks in cover of individual species at these edges. Our results suggest that expansion of tree islands and krummholz would affect the abundance of tundra plant species, which could lead to changes in species composition and biodiversity. On s’attend à ce que l’écotone de la toundra forestière subisse dans une certaine mesure les premiers effets du changement climatique. À l’avant-plan de cette zone de transition se trouvent des formes de croissance clonales d’arbres rabougris et difformes parfois assortis ou non assortis de plus grands arbres dressés, ce que l’on appelle des îlots boisés et des krummholz, respectivement. Nous avons cherché à évaluer les effets potentiels de l’expansion de ces formes de croissance clonales sur les espèces végétales de la toundra à deux emplacements situés au Canada, un aux monts Mealy du Labrador et l’autre près de Churchill, au ...